Udział wyższych uczelni w realizacji projektów finansowanych ze środków europejskiego funduszu społecznego - Kwiatkowska-Ciotucha, Dorota (Participation of Polish University in Project Financing from European Social Funds, 2008)
Summary The paper presents results of the analysis of possibilities connected with projects' realization financed from European Social Funds provided by university. Some experiences from the first period of structural funds realization in Poland are discussed. In the research some barriers and threads arising in parlicular step of projec's realization are presented. Proposals planned for the period of 2007-2013 are also described. For the illustration, some experiences from project realization in the Wroclaw University of Economics are presented and discussed. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 130-139